2012
DOI: 10.1631/jzus.b1201005
|View full text |Cite
|
Sign up to set email alerts
|

Renal insufficiency is an independent predictor of in-hospital mortality for patients with acute myocardial infarction receiving primary percutaneous coronary intervention

Abstract: Renal insufficiency is an independent predictor of in-hospital mortality for patients hospitalized with ASTEMI treated with primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…For patients with STEMI treated with primary PCI, it is known that renal insuffi ciency is an independent predictor of in-hospital mortality [37,38]. The results of the present study did not confi rm it.…”
Section: Discussioncontrasting
confidence: 89%
“…For patients with STEMI treated with primary PCI, it is known that renal insuffi ciency is an independent predictor of in-hospital mortality [37,38]. The results of the present study did not confi rm it.…”
Section: Discussioncontrasting
confidence: 89%
“…[12] However, the in-hospital mortality rate in the CKD group was higher than that previously reported (21.32% vs 8.7%). [11] This might be because our study population was enrolled from real-world setting without preselection. In contrast, patients with severe renal dysfunction were excluded from the study conducted by Li et al [11] In addition, all patients in the previous study had received primary PCI treatment, compared with 6.09% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study done by Jian-Ping et al, 14 included 420 patients of ACS found that death was 1.67% in group A, 8.20% in group B and 20% in group C (p-value 0.001). In comparison to above study, in our study there is more mortality in group A and C, and almost same mortality in group B.…”
Section: Discussionmentioning
confidence: 63%